2006
DOI: 10.1111/j.1600-0420.2006.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity and disability glare in patients with dry eye

Abstract: . Purpose:  To evaluate contrast sensitivity and disability glare in patients with dry eye using the Contrast Glaretester 1000. Methods:  Contrast sensitivity and disability glare were determined in 33 eyes of 33 patients with dry eye and 30 eyes of 30 healthy control subjects for six target sizes with a visual angle of 6.3–0.7 degrees using the Contrast Glaretester 1000, whose working mechanism is similar to that of the conventional perimetry instrument. Results:  Contrast sensitivity was significantly worse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Dry eye patients with visual impairment or symptoms in everyday life are reported to have decreased contrast sensitivity which reduces their ability to appreciate subtle differences in color or shape under low light or indirect bright-light conditions [2][3][4][5]. It is also reported that irregularity of the ocular surface contributes to glare disability and that this glare disability may be reflecting visual disability in the early phase of dry eyes, such as dry eye without punctuate epithelial keratopathy [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dry eye patients with visual impairment or symptoms in everyday life are reported to have decreased contrast sensitivity which reduces their ability to appreciate subtle differences in color or shape under low light or indirect bright-light conditions [2][3][4][5]. It is also reported that irregularity of the ocular surface contributes to glare disability and that this glare disability may be reflecting visual disability in the early phase of dry eyes, such as dry eye without punctuate epithelial keratopathy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies reported measurement of visual acuity over a 30-s interval under forced eye opening and topical anesthesia with eye drops [7][8][9][10]. It is, however, questionable whether visual acuity measured after the application of topical anesthesia actually reflects the acuity status under natural conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,30 -32 Glare test may be also a useful method of reflecting visual disability. 25,26 It was reported that irregularity of the ocular surface contributes to glare disability in the early phase of dry eye disease such as in dry eyes without SPK. 25,26 Functional visual acuity (VA), which evaluates the time-wise changes in VA, can also be a helpful method of detecting the masked impairment of visual performance in dry eye patients who report decreased VA despite showing normal VA in standard VA testing.…”
mentioning
confidence: 99%
“…Contrast sensitivity is considered an accurate method of measuring the quality of vision in patients with dry eye syndrome. [23][24][25][26][27][28][29] It has been reported that contrast sensitivity is decreased in dry eye patients with the impaired ability to appreciate subtle differences in color or shape under low light or indirect bright-light conditions. 24,30 -32 Glare test may be also a useful method of reflecting visual disability.…”
mentioning
confidence: 99%